Estudo cronológico de mamíferos pleistocênicos de Sergipe, Brasil - França, Lucas de Melo (2014)
The number of mammals species belonging to the Pleistocene megafauna (animals with more than 44 kg) registered for Sergipe state is still low compared with other states from Brazilian Intertropical Region (BIR). In this study, fossils found in fossiliferous outcrops (Tanks) in the Charco and São José Farm (municipality of Poço Redondo, Sergipe) and Elefante Farm (município de Gararu, Sergipe) localities were analysed. This study described fossils of taxa already registered for the state, like Eremotherium laurillardi, Notiomastodon platensis, Smilodon populator, Mylodontidae and Toxodontinae, besides registering for the first time Xenorhinotherium bahiense, increasing the number of taxa known in Sergipe. Besides the description of fossils, this study also provided absolute dating and isotopes analyses for E. laurillardi e N. platensis from São José Farm (Poço Redondo, Sergipe) tank, contributing for the knowledge about the chronology of this species in BIR, their paleodiets and the environment where they lived during the final Pleistocene. The results showed that the mastodont N. platensis occurred between 12.125 and 19.594 cal yr BP and exhibited a grazer diet (d13C = -1.1 to 1.3 ), while the giant sloth E. laurillardi lived between 11.084 and 13.581 cal yr BP, with a mixed feeder diet (C3/C4 plants; values ratio d13C = -7.7 to -3.3 ). The d18O values of N. platensis ranged between 31.1 to 34.7 , while the values of E. laurillardi ranged between 27.7 to 29.7 , but in both cases the species where inhabiting an environment with high temperatures. The compilation of the data available for this species in this region allows the conclusion that neither species did exhibit differences in its diet through the last thousand of years of the final Pleistocene, which suggests that the vegetational composition of this locality did not vary during this period.